2003
DOI: 10.1161/01.cir.0000097119.57756.ef
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cells in Human Atherosclerotic Plaques Express the Fractalkine Receptor CX 3 CR1 and Undergo Chemotaxis to the CX 3 C Chemokine Fractalkine (CX 3 CL1)

Abstract: Background-Chemokines are important mediators of inflammatory cell recruitment that play a significant role in atherosclerosis. Fractalkine (CX 3 CL1) is an unusual membrane-bound chemokine that mediates chemotaxis through the CX 3 CR1 receptor. Recently, functional polymorphisms in the human CX3CR1 gene have been described that are associated with coronary artery disease. Methods and Results-We investigated the expression of the CX 3 C chemokine fractalkine and its receptor CX 3 CR1 in human coronary artery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 48 publications
10
117
1
1
Order By: Relevance
“…20 Monocyte adhesion and arrest on neointimal SMC is dependent on CX 3 CL1, 21 and VSMCs undergo chemotaxis toward CX 3 CL1. 17 Thus, CX 3 CL1 may act not only on monocytes, but also may function to stimulate SMC proliferation and recruitment into the neointima.In the present study, we employed an endoluminal arterial injury model to investigate the role of CX 3 CR1 in the pathogenesis of vascular injury. This model elicits a stereotypic response that allows for assessment of the functional roles of platelets, monocytes, and VSMCs.…”
mentioning
confidence: 99%
“…20 Monocyte adhesion and arrest on neointimal SMC is dependent on CX 3 CL1, 21 and VSMCs undergo chemotaxis toward CX 3 CL1. 17 Thus, CX 3 CL1 may act not only on monocytes, but also may function to stimulate SMC proliferation and recruitment into the neointima.In the present study, we employed an endoluminal arterial injury model to investigate the role of CX 3 CR1 in the pathogenesis of vascular injury. This model elicits a stereotypic response that allows for assessment of the functional roles of platelets, monocytes, and VSMCs.…”
mentioning
confidence: 99%
“…Reports by Lucas et al (33) have indicated that aortic smooth muscle cells, another type of specialized mesenchymal cells, utilize the CX 3 CR1-FKN pathway for proliferation control. In vitro, the soluble form of FKN promotes aortic smooth muscle cell proliferation through NF-B signaling (34).…”
Section: Discussionmentioning
confidence: 99%
“…Within the vasculars ystem CX3CL1 has beenl ocated on endothelial cells and smoothm uscle cells (SMCs) in situ (33). CX3CL1and CXCL16 were found to be induced in both celltypes in vitro upon activation with proinflamatorymediators(reviewed in [34]).…”
Section: Proteolytic Conversion Of Transmembrane Chemokinesmentioning
confidence: 99%
“…Atherosclerosis is characterized by increased infiltration of leukocytesinparticularmonocytic cells in the vascular wall. Intimalm acrophages within atherosclerotic lesions have beenfound to express CX3CL1 and CXCL16 (33,(42)(43)(44)89). CX3CL1 is also profoundlye xpressed by SMCs in the media of humancoronary arteries (33).…”
Section: 'Specialagents' Promotingvascular Inflammationmentioning
confidence: 99%
See 1 more Smart Citation